Interest rates, income distribution and the monetary policy transmissions mechanism under endogenous money: what have we learned 30 years on from Horizontalists and Verticalists? - John Smithin (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
This paper suggests that the near-optimal setting of the real policy rate of interest (the real overnight rate in Basil Moore's home country of Canada) is zero. This will achieve as close an approximation as possible to a fair distribution of income in a particular sense. It will also promote financial stability, inflation stability, high growth, full employment and higher real wages.
Keywords: B12; B22; B26; E13; E43; E58; 330; Basil J. Moore; endogenous money; income distribution; monetary policy transmissions mechanism; zero interest rate policy (ZIRP); zero real policy rate (ZRPR)